The guanine nucleotide exchange factor p63RhoGEF, a specific link between Gq/11-coupled receptor signaling and RhoA - Lutz, Susanne; Freichel-Blomquist, Andrea; Yang, Yang; Rümenapp, Ulrich; Jakobs, Karl-Heinz; Schmidt, Martina; Wieland, Thomas (The journal of biological chemistry, 2005)
The monomeric GTPase RhoA, which is a key regulator of numerous cellular processes, is activated by a variety of G protein-coupled receptors, through either G12 or G(q) family proteins. Here we report that p63RhoGEF, a recently identified RhoA-specific guanine nucleotide exchange factor, enhances the Rho-dependent gene transcription induced by agonist-stimulated G(q/11)-coupled receptors (M3-cholinoceptor, histamine H1 receptor) or GTPase-deficient mutants of G alpha(q) and G alpha11. We further demonstrate that active G alpha(q) or G alpha11, but not G alpha12 or G alpha13, strongly enhances p63RhoGEF-induced RhoA activation by direct protein-protein interaction with p63RhoGEF at its C-terminal half. Moreover, the activation of p63RhoGEF by G alpha(q/11) occurs independently of and in competition to the activation of the canonical G alpha(q/11) effector phospholipase C beta. Therefore, our results elucidate a new signaling pathway by which G alpha(q/11)-coupled receptors specifically induce Rho signaling through a direct interaction of activated G alpha(q/11) subunits with p63RhoGEF.